Postoperative Pro-Adrenomedullin Levels Predict Mortality in Thoracic Surgery Patients. Issue 2 (February 2015) - Schoe, Abraham; Schippers, Emile F.; Struck, Joachim; Ebmeyer, Stefan; Klautz, Robert J.M.; de Jonge, Evert; van Dissel, Jaap T.
<x xml:space="preserve">Abstract</x> Objectives: Risk assessment in ICU patients using commonly used prognostic models may be influenced using different data definitions and by errors in data collection. We investigated whether a set of biomarkers (procalcitonin, MR-pro-adrenomedullin, CT-pro-endothelin-1, CT-pro-arginine vasopressin, and MR-pro-atrial natriuretic peptide), alone or as a panel, could be useful in postoperative risk assessment for hospital mortality in comparison with the Acute Physiology and Chronic Health Evaluation IV score. Design: In a prospective observational cohort study, we analyzed 800 consecutive patients undergoing elective cardiac surgery. We assessed biomarker levels on admission to the ICU and every 6 hours thereafter for 24 hours. For every postoperative time point and for every biomarker, we determined the predictive value for hospital mortality and made a comparison with the Acute Physiology and Chronic Health Evaluation IV score. Setting: Intensive care of an academic referral hospital. Patients: A total of 800 consecutive patients undergoing elective cardiac surgery. Interventions: None. Measurements and Main Results: MR-pro-adrenomedullin is a good predictor of mortality (c-statistic at time point 6 hr after admission to the ICU, 0.940; 95% CI, 0.918–0.956) and performed better than the Acute Physiology and Chronic Health Evaluation IV score (c-statistic, 0.842; 95% CI, 0.811–0.868). The c-statistic did not change significantly on the time points 6, 12, and 18 hours after admission. Using a cutoff value for proadrenomedullin taken 6 hours after admission on ICU (time point 2) of 3.2 nmol/L sensitivity was 81.8% and specificity 93.9%, the positive likelihood ratio was 13.3, positive predictive value was 31.0%, and negative predictive value was 99.4%. Patients with a MR-pro-adrenomedullin above this cutoff level had an odds ratio of 68.9 (95% CI, 22.2–213.1) for not surviving their hospital stay. The other biomarkers had less predictive power. Conclusions: In elective cardiac surgery, MR-pro-adrenomedullin measured between 6 and 18 hours after admission to the ICU is a better predictor of hospital mortality in comparison with the Acute Physiology and Chronic Health Evaluation IV score.